2022
DOI: 10.3389/fdata.2022.805713
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Gender Bias in Job Advertisements With Text-Level Bias Mitigation

Abstract: Despite progress toward gender equality in the labor market over the past few decades, gender segregation in labor force composition and labor market outcomes persists. Evidence has shown that job advertisements may express gender preferences, which may selectively attract potential job candidates to apply for a given post and thus reinforce gendered labor force composition and outcomes. Removing gender-explicit words from job advertisements does not fully solve the problem as certain implicit traits are more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For example, the computational team found that, by collaborating closely with the sociology team, they were able to solidify concepts and methods, and make their analysis more meaningful. This process informed work on a paper where the sociology team took the lead in developing a list of gender-related words in job advertisements, which the computing team then used to refine their approach to gender bias mitigation (Hu et al, 2022). As explained by a computing team member: 'Although we could, probably, rely on common sense, we don't have to in this project.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the computational team found that, by collaborating closely with the sociology team, they were able to solidify concepts and methods, and make their analysis more meaningful. This process informed work on a paper where the sociology team took the lead in developing a list of gender-related words in job advertisements, which the computing team then used to refine their approach to gender bias mitigation (Hu et al, 2022). As explained by a computing team member: 'Although we could, probably, rely on common sense, we don't have to in this project.…”
Section: Methodsmentioning
confidence: 99%
“…Research has provided clear evidence that job postings, explicitly and implicitly, signal employers' preferences for certain types of candidates, which may lead to potential gender biases. There is an indication that the language and wording used in UK STEM job advertisements are biased toward a masculine orientation [29]; and even that there is a positive association between male-biased job postings and a male-dominated STEM workforce [30].…”
Section: Gender Biases In Job Postings and Theoriesmentioning
confidence: 99%
“…They may work to preemptively analyze existing materials for racialized or gendered language (Hu et al, 2022) as well as work to emphasize skills rather than "fit" (Palmer and Mullooly, 2015).…”
Section: Recruitmentmentioning
confidence: 99%